Internal and External e-Customs Services IOS Application Case Study: Kuwait Customs Department - Soha Aljaber; Nayfah Mohsen Almutairi; Abdulrahman Alkandari (Institute of Advanced Engineering and Science, 2018)
Government regulations usually characterized by the many stages of completion of any transaction and that causing a delay in the work and that wasting a lot of time. Especially with the particular customs system which consists of several points of entry, including land, sea, and air. In addition, the General Customs Department is one of the sensitive circuits in the state. Therefore, to continue the process any shipment or any transaction relating to customs, it requires a long time. This paper presented a design for an application that running on smartphones with IOS system. This application provides internal services and external services for the General Customs Department to ease the completion of any transaction either for the customs’ employee or the citizens. The employee uses the internal services section, and the external services section is used by the citizens. As a result of this application, it provides time and effort for the citizens and customs and decreasing the number of customs’ reviewers.